Efficient removal of tetracycline from aqueous solution by K2CO3 activated penicillin fermentation residue biochar - Liu, Yanfang; Gao, Wei; Yin, Sijie; Liu, Rui; Li, Zaixing (Frontiers in Chemistry, 2022)
In this study, biochar was prepared using penicillin fermentation residue (PR) as the raw material by different methods. The adsorption behavior and adsorption mechanism of biochar on tetracycline (TC) in an aqueous environment were investigated. The results showed that K2CO3 as an activator could effectively make porous structures, and that biochar with mesoporous or microporous could be prepared in a controlled manner with two kinds of different activation methods, the dry mixing method and the impregnation method. The dry mixing method could create more mesopores, while the impregnation method could prepare more micropores. Microporous biochar (IKBCH) with a high specific surface area could be prepared by the impregnation method combined with HCl soaking, which has an excellent adsorption effect on tetracycline. When the concentration of tetracycline was 200 mg/L, the removal rate of 99.91% could be achieved with the dosage of microporous biochar at 1 g/L. The adsorption process was in accordance with the Langmuir model and the pseudo-second-order model, respectively. The maximum adsorption capacity of IKBCH was 268.55 mg/g (25°C). The adsorption mechanisms were pore filling, π-π interaction, electrostatic adsorption, and hydrogen bond. Its stable and wide applicability adsorption process does not cause ecological pollution in the aqueous environment, and it is a promising biochar adsorbent.